Implementasi senam ceria dalam pembelajaran PJOK untuk meningkatkan kecerdasan kinestetik pada Siswa Sekolah Dasar - Pajar Anugrah Prasetio; Arrofa Acesta; Dian Damayanti; Febby Fajar Nugraha (IKIP Siliwangi, 2023)
This research is motivated by the low ability to kinesthetic intelligence in students, because students are not confident, low cognitive skills and active and creative thinking patterns are still low. Considering how important kinesthetic intelligence is in elementary school students. This researcher aims to describes the implementation of cheerful gymnastics to improve kinesthetic intelligence in students. This research method used is pre-eksperimental with a design one group pretest posttest design with a class IV of 12 students. Collecting data used in this study was a test instrument work method. Based on the results of the average score of students in the pretest, which was 55,5 and the average score of the posttest, which was 81,75 it showed that the average score of the student was different, including the average score of the pretest before being given treatment and the average score of the posttest after being given treatment. This is proven through the t test stating that the calculation (10,39) > ttabel (2,074) at a significant level of 5% then HO is rejected and H1 is accepted. And for the N-gain score test (0,6) the percent N-gain (60%) is in the medium category. Thus, it can be concluded that there an cheerful gymnastics is effective in increasing kinesthetic intelligence in grade IV students in SD Negeri 11 Kuningan.